Filipino English and Taglish : language switching from multiple perspectives - Thompson, Roger M. (Varieties of English around the world. General series, 2003)
English competes with Tagalog and Taglish, a mixture of English and Tagalog, for the affections of Filipinos. To understand the competing ideologies that underlie this switching between languages, this book looks at the language situation from multiple perspectives. Part A reviews the social and political forces that have propelled English through its life cycle in the Philippines from the 1898 arrival of Admiral Dewey to the 1998 election of Joseph Estrada. Part B looks at the social support for English in Metro Manila and the provinces with a focus on English teachers and their personal and.